Gastric Signet-Ring Cell Carcinoma Metastasis to Bilateral Ovarian Granulosa Cell Tumors. (March 2015) - Shi, Lin; Guo, Zhanlin; Wei, Xuan; Jia, Yongfeng; Bao, Luri; Lu, Jianjun
Abstract : Tumor-to-tumor metastasis is a rare phenomenon. On the basis of our review of international literature, there have been 7 reports of tumor-to-tumor metastasis cases involving ovary neoplasms as the recipient. However, an ovarian granulosa cell tumor has not been reported to be a recipient. Here, we report the first case of gastric signet-ring cell carcinoma metastasis to a bilateral ovarian granulosa cell tumor. Awareness of this phenomenon is important to avoid incorrect diagnoses when encountering unusual morphologic features in ovarian granulosa cell tumors.